Основи освітньої інноватики : методичні рекомендації до проведення семінарських і практичних занять, організації самостійної роботи здобувачів третього (освітньо-наукового) рівня вищої освіти зі спеціальності 011 «Освітні, педагогічні науки» - Ткачова, Наталія Олександрівна; Ткачов, Артем Сергійович; Байдала, Вікторія Вікторівна; Чирва, Ярослава Олександрівна; Tkachova, Nataliia Oleksandrivna; Tkachov, Artem; Baidala, Viktoriia; Chyrva, Iaroslava (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
Методичні рекомендації до навчального модуля «Основи освітньої інноватики» як складника інтегрованого навчального курсу «Основи освітньої інноватики. Медіаосвіта. Цифровізація освітньо-наукового простору» містять навчальні й дидактичні матеріали для проведення семінарських і практичних занять, організації самостійної роботи здобувачів третього (освітньо-наукового) рівня вищої освіти зі спеціальності 011 Освітні, педагогічні науки.

Methodical recommendations for the educational module ‘Fundamentals of Educational Innovation’ as a component of the integrated course ‘Fundamentals of Educational Innovation. Media education. Digitalisation of the Educational and Scientific Space’ contain educational and didactic materials for seminars and practical classes, organisation of independent work of applicants for the third (educational and scientific) level of higher education in the speciality 011 Educational, Pedagogical Sciences.
Fundamentals of educational innovation: methodical recommendations for conducting seminars and practical classes, organising independent work of applicants for the third (educational and scientific) level of higher education in the speciality 011 Educational, pedagogical sciences
Keywords: SOCIAL SCIENCES::Social sciences::Education; освітня інноватика; інноваційний освітній процес; інноваційна професійна діяльність; інноваційний заклад освіти; educational innovation; educational innovation; innovative educational process; innovative professional activity; innovative educational institution